Exploratory and confirmatory factor analysis of the parental rules toward adolescent drinking questionnaire: Two factors are better than the original one. (June 2021) - Trager, Bradley M.; Koning, Ina M.; Turrisi, Rob
Highlights: Psychometric evaluation of the Parental Rules toward Drinking Questionnaire (PRQ). EFA and CFA revealed two reliable subscales: normative and non-normative rules. PRQ subscales were positively correlated with adolescent alcohol use. PRQ subscales revealed effects on drinking not found with total PRQ. Implications for prevention efforts are to prohibit normative drinking situations. Abstract: The parental rules toward drinking questionnaire (PRQ; Van der Vorst et al., 2005) assesses strictness toward adolescent drinking situations. The aim of the current study was to address a gap in the literature on the psychometric testing and evaluation of the factor structure of the PRQ. The current sample consisted of Dutch adolescents ( N  = 2922) who participated in a randomized control trial with three intervention groups (parent, student, and parent + student) and a control. PRQ and frequency of alcohol use (past month and year) were measured at baseline (T1) and 12 months later (T2). Results from Exploratory and Confirmatory Factor Analyses revealed two reliable factors: (a) rules about normative drinking situations and (b) rules about non-normative drinking situations (both α s ≥ 0.88). Regression analyses conducted to examine the prospective effects of the interventions revealed that both parent conditions predicted increases in strictness toward normative drinking situations relative to the control condition, while only the parent + student condition affected the original PRQ (single factor). Further, the normative subscale predicted increases in drinking (past month and year), as did the original PRQ. Significant effects with the normative subscale indicate that rules toward these drinking situations are ones that account for the effects in the original PRQ, and that the original PRQ can mask effects. The results illustrate that the PRQ is multidimensional. The effects of the normative subscale suggest that intervention efforts should focus on preventing drinking situations that parents normally permit their adolescents to engage in.